2010
DOI: 10.1016/j.bbamem.2010.02.027
|View full text |Cite
|
Sign up to set email alerts
|

PEP and CADY-mediated delivery of fluorescent peptides and proteins into living cells

Abstract: Cell-penetrating peptides (CPPs) constitute a family of peptides with the characteristic ability to cross biological membranes and deliver cargo into the intracellular milieu. Several CPPs have been proposed for delivery of polypeptides and proteins into cells through either of two strategies: covalent or complexed in a non-covalent fashion. Members of the PEP family are primary amphipathic peptides which have been shown to deliver peptides and proteins into a wide variety of cells through formation of non-cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 69 publications
3
80
1
Order By: Relevance
“…32,33 The environmental and conformational change that EGFP undergoes upon binding of a ligand often causes a measurable change in its fluorescence emission, making it a good reporter for this binding assay. 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…32,33 The environmental and conformational change that EGFP undergoes upon binding of a ligand often causes a measurable change in its fluorescence emission, making it a good reporter for this binding assay. 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…Light scattering experiments and electron microscopy have shown that biologically active Pep-1/cargo complexes form homogeneous nanoparticles (100-200 nm diameters). The use of higher ratios generally led to form larger particles or aggregates that are poorly taken up by cells and tend to accumulate on the cell surface or within endosomes (30). A study showed that biologically efficient complexes of Pep-1/p27Kip tumor suppressor were formed as discrete particles with an average size of 96 6 19 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Pep-1 peptide was designed from three components including a hydrophobic N-terminal domain (a tryptophan rich motif) for interaction with proteins and efficient targeting to the cell membrane, a hydrophilic C-terminal domain (KKKRKV) for solubility and intracellular delivery, and a short linker (SQP) for improvement of the flexibility and the integrity of both domains (28,30). The addition of acetyl (Ac) and cysteamide (Cy) groups at the N-/C-terminal regions of Pep-1 were also proposed to stabilize the cargo-carrier complexes and its transduction mechanism (30,31).…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Besides microinjection, electroporation or cell-loading approaches which apply mechanical stress on the cell membrane [71], transduction of peptide and protein biosensors into living cells can be achieved thanks to peptide-based carriers such as protein-transduction domains or cell-penetrating peptides, which are either covalently fused (e.g., TAT), conjugated or complexed into non-covalent nanoparticles [72,73,74,75]. In addition lipid-based formulations, cationic and polymeric carriers, as well as silica-based nanoparticles or carbon nanotubes offer plenty of platforms to ensure delivery of peptide and protein biosensors into cells [76,77,78].…”
Section: Probing Protein Kinase Activities In Vitro With Peptide Amentioning
confidence: 99%
“…More recently, the CDKACT protein-biosensor was introduced into living cells through complexation with cell-penetrating peptides that form nanoparticles with their cargo and ensure its efficient and non-covalent intracellular delivery [38,74]. These formulations enabled application of CDKACT to monitor oscillations in CDK/Cyclin activity throughout the cell cycle by time-lapse imaging and ratiometric quantification of Cy5 and RFP fluorescence, the former conjugated to the substrate sequence and responding to kinase activity, the latter serving as an intramolecular control.…”
Section: Probing Protein Kinase Activities In Vitro With Peptide Amentioning
confidence: 99%